Discharge Planning and Its Impact on Patient Outcomes: A Systematic Review - Rahman, Wahyudin Abd; Chanif, Chanif; Samiasih, Amin (Jurnal Ners, 2025)
Latar Belakang: Discharge planning adalah proses penting dalam transisi perawatan yang bertujuan meningkatkan kualitas hidup pasien, mengurangi rehospitalisasi, dan memperkuat kesiapan pasien serta keluarga. Namun, implementasinya di berbagai fasilitas kesehatan belum optimal. Metode: Studi ini merupakan systematic review berdasarkan pedoman PRISMA. Pencarian artikel dilakukan pada database Google Scholar, ProQuest, PubMed, ScienceDirect, dan SpringerLink dengan kata kunci: “discharge planning” OR “hospital discharge” OR “patient outcomes” OR “readmission” OR “rehospitalization”, dalam rentang tahun 2020–2024. Dari 294 artikel, 10 artikel dipilih setelah melalui proses seleksi. Hasil: Discharge planning berdampak positif terhadap kualitas hidup, kesiapan pulang, dan penurunan rehospitalisasi. Faktor pendukungnya meliputi motivasi perawat, supervisi, dan kepemimpinan. Hambatan utama adalah beban kerja tinggi dan kurangnya dokumentasi. Kesimpulan: Discharge planning yang efektif membutuhkan dukungan sistem, keterlibatan perawat, dan pendekatan yang responsif terhadap kebutuhan pasien. Implementasi yang terstruktur dapat meningkatkan luaran pasien dan efisiensi layanan kesehatan. Kata Kunci: Discharge planning, rehospitalisasi, kesiapan pulang, luaran pasien, supervisi keperawatan Abstract Introduction: Discharge planning is a critical process in care transition aimed at improving patients’ quality of life, reducing rehospitalization, and enhancing the readiness of both patients and families. However, its implementation remains suboptimal across various healthcare facilities. Methods: This study is a systematic review conducted based on the PRISMA guidelines. Article searches were performed in Google Scholar, ProQuest, PubMed, ScienceDirect, and SpringerLink using the keywords: “discharge planning” OR “hospital discharge” OR “patient outcomes” OR “readmission” OR “rehospitalization”, with a publication range from 2020 to 2024. Out of 294 identified articles, 10 were selected after screening and eligibility assessment. Results: Discharge planning has a positive impact on quality of life, discharge readiness, and reduced rehospitalization rates. Supporting factors include nurse motivation, supervision, and leadership. Main barriers are high workload and lack of documentation. Conclusion: Effective discharge planning requires system support, active nurse involvement, and a patient-centered approach. Structured implementation can improve patient outcomes and healthcare service efficiency. Keywords: Discharge planning, rehospitalization, discharge readiness, patient outcomes, nursing supervision.